Formulation and Physical Characteristics of Effervescent Granules from Sunkist Peels Ethanol Extract - Maya Sari Mutia; Stephanie Raibalaki; Siti Rahma; Anita Zahra; Ali Napiah Nasution; Widya Yanti Sihotang (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Citrus fruit has a sweet taste and attractive shape, which is also enriched various health benefits. Some studies have been performed to investigate the pharmacology effects from the Sunkist peel extract. However, none of this study was look for the development of pharmaceutical products. Hence this study was performed to investigate the pharmaceutical formulation as an effervescent granule from Sunkist peel extract. This study was an experimental study to investigate the optimum formulation that was made by wet granulation methods. There were three formulation of Sunkist peel extract effervescent granule that were combination of organic acids (citric acid and tartaric acid), sodium bicarbonate as base compound, and some sweetener including aspartame, lactose, and mannitol. After that, the formulation was evaluated the physical properties including organoleptic, flow rate, dissolution time, foam height, pH, and angle of repose. The result of this study showed that these three formulations of Sunkist Peel extract effervescent granule showed significant different in almost all of physical properties including: flow rate (P-Value = 0.027), dissolution time (P-Value less than 0.05), foam height (P-Value = 0.004), and angle of repose (P-Value: 0.043), except the degree of acidity or pH (P-Value = 0.128). Third formulation (F3) reveals the best physical properties as a Sunkist peel extract effervescent granule. Overall, it can be concluded that the third and second formulation fulfils a well physical properties of effervescent granule for Sunkist peel extract.